States against migrants deportation in Germany and the United States - Ellermann, Antje 1971- (Cambridge, [England] Cambridge University Press, 2009)
"In this comparative study of the contemporary politics of deportation in Germany and the United States, Antje Ellermann analyzes the capacity of the liberal democratic state to control individuals within its borders. The book grapples with the question of why, in the 1990s, Germany responded to vociferous public demands for stricter immigration control by passing and implementing far-reaching policy reforms, wheras the United States failed to respond effectively to a comparable public mandate."--Page [i]
List of figures -- Acknowledgments -- Introduction: Deportation and the state -- A theory of socially coercive state capacity -- The legislative politics of migration control -- Deportation and the executive politics of implementation -- Deportation and the street-level politics of implementation -- Conclusion.
Includes bibliographical references (pages 177-189) and index.
Keywords: Deportation -- United States; Deportation -- Germany; United States -- Emigration and immigration; Germany -- Emigration and immigration